SOSIALISASI PENCEGAHAN STUNTING MELALUI PENGENALAN POTENSI PANGAN LOKAL DI DESA TAPALINNA, KECAMATAN MAMBI, KABUPATEN MAMASA - Hamjan, Dewi Febriani; Nur, Hardianti; Utami, Widya; Binayanti, Binayanti; Aulia, Riska; Marlinda, Marlinda; Arkarna, Adiba; Lestari, Amanda Nurpuspita; Felisa, Nesa Ratu; Darmi, Darmi; Candra, Muh, Agung; Feri, Feri; Hidayat, Muh; Yegar, Yegar (Universitas Mataram, 2025)
Stunting is a chronic nutritional problem that impacts children's physical growth and cognitive development. In Mamasa Regency, the prevalence of stunting remains well above the WHO threshold, indicating the need for sustained intervention. Low nutritional knowledge and minimal use of local foods, such as tilapia, contribute to the worsening situation. Tilapia, however, boasts high nutritional content and has the potential to be an affordable and accessible nutritional solution. This activity aims to raise public awareness about stunting prevention by promoting the benefits of tilapia as a highly nutritious local food source that supports children's nutritional needs. The community service activity was carried out in Tapalinna Village using a participatory approach through observation, pre-tests, seminars, and interactive education. The main focus of the activity was promoting stunting prevention by introducing tilapia as a nutritious local food. The Community Service Program (PKM) activity demonstrated the significant potential of tilapia (Oreochromis niloticus) as a local protein source. Pre-tests revealed low understanding among participants about stunting and the importance of nutrition, particularly animal protein. Education through seminars and tilapia processing demonstrations successfully increased public knowledge and enthusiasm. Diversifying tilapia products is a solution to increase children's interest in consuming tilapia. Nutrition leaflets and practical recipes strengthened participants' understanding. The results of the activity demonstrated that an educational approach based on local food is effective in supporting stunting prevention. The use of tilapia as a nutritious local food increased community understanding and supported effective and sustainable stunting prevention.